2012
DOI: 10.1002/ar.22485
|View full text |Cite
|
Sign up to set email alerts
|

The Prenatal Toxic Effect of Methylmercury on the Development of the Appendicular Skeleton of Rat Fetuses and the Protective Role of Vitamin E

Abstract: Methylmercury (MeHg) is an environmental contaminant that is found in many ecosystems. Many studies reported that MeHg toxicity is accompanied by increased lipid peroxidation that may lead to oxidative damage to DNA, RNA, and proteins. Vitamin E is considered as the most effective antioxidant preventing lipid peroxidation. The aim of this study was to evaluate the effects of MeHg exposure during pregnancy on the development of the appendicular skeleton in rat fetuses and whether vitamin E administration could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…In line with the use of antioxidant and folic acid therapy for reduction of the frequency and severity of AEDinduced teratogenic effects, it was found that concomitant vitamin E administration significantly attenuated valproic acid and phenytoin induced decrease in crown-rump length, fetal weight and malformations [26,28,39]. The study of Abd El-Aziz et al [36] showed that the co-administration of vitamin E with MeHg was also associated with an improvement in the fetal crown-rump length, body weight, head length, and biparietal diameter of the rat fetuses. The study of Abou-El-Naga [52] on pregnant mice injected with polycyclic hydrocarbons and curcumin from the GD 6 till the parturition showed improved neonatal growth retardation and reduced malformation rate.…”
Section: Administration Of Vigabatrin and Valproic Acid To 4-mentioning
confidence: 85%
See 1 more Smart Citation
“…In line with the use of antioxidant and folic acid therapy for reduction of the frequency and severity of AEDinduced teratogenic effects, it was found that concomitant vitamin E administration significantly attenuated valproic acid and phenytoin induced decrease in crown-rump length, fetal weight and malformations [26,28,39]. The study of Abd El-Aziz et al [36] showed that the co-administration of vitamin E with MeHg was also associated with an improvement in the fetal crown-rump length, body weight, head length, and biparietal diameter of the rat fetuses. The study of Abou-El-Naga [52] on pregnant mice injected with polycyclic hydrocarbons and curcumin from the GD 6 till the parturition showed improved neonatal growth retardation and reduced malformation rate.…”
Section: Administration Of Vigabatrin and Valproic Acid To 4-mentioning
confidence: 85%
“…In developmental studies, the fetal skeleton is an important indicator of embryonic development health and changes in skeletal development commonly reflect changes in the maternal-fetal environment [36]. Fetuses maternally injected with GBP had various skeletal malformations including mandibular hypoplasia, malformation in the ribs and delayed ossification of the vertebrae, skull and limbs.…”
Section: Endo-skeletal Investigationmentioning
confidence: 99%
“…Mercury is a teratogen, with no known mutagenic action; it transpasses the placenta [37,38,39,40], interferes in key pathways in development [42,43,44]: Notch pathway [42], modulation of key enzymatic antioxidant and oxidative stress makers [44,45]; it affects sperm phenotypes [46], and various organ compartments during rat embryogenesis [47,48], and is neurotoxic [17,49]. Mercury is an endocrine disruptor and affects spermatogenesis, causes malformations and reproductive damages in mammals and human [10,50].…”
Section: Resultsmentioning
confidence: 99%
“…The treatment of vitE has been found to alleviate toxic hematological effects of CN induced oxidative stress in broiler chicks (Sharaf et al, 2010;Aslam et al, 2010). Moreover, the decreased skeletal ossification in fetal rats on methyl mercury exposure has been found to be reversed with vitE treatment (Abd et al, 2012).…”
Section: Research Articlementioning
confidence: 98%